Penerapan Media Powtoon dalam Pembelajaran Teks Negosiasi Peserta Didik Kelas X-4 SMA N 5 Semarang - Amalia, Ana; Ngatmini, Ngatmini (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Learning media is a component that supports effectiveness in the learning process in Indonesian language subjects. In applying media in learning, teachers are advised to apply media that can make students interested in learning and raise their motivation in learning. As technology develops in the current digital era, there are more and more technology-based learning media. Powtoon media is a technology-based learning media that can attract students to learn and raise their motivation. This is because the media is an animated video that combines audio and visuals which can provide a special attraction in learning negotiation texts for class X-4 students. This research examines the application of Powtoon media in learning negotiation texts for class X-4 students at SMA N 5 Semarang. The main problem is the low interest of students in learning about negotiation text material which is delivered only through the lecture method without interactive learning media. Therefore, researchers apply new innovations in the learning process in the form of applying Powtoon media in learning negotiation texts with the aim of increasing activity so that students are more enthusiastic and active in learning, in addition to making students understand more about the structure of negotiation texts Powtoon media. The research method used is descriptive qualitative with data collection through tests and non-tests. The research results show that the application of Powtoon is effective in increasing student participation, this is shown by the test results of students with the highest score of 95 and the lowest score of 85, and non-test results in the form of interviews and observations show that students are active and enthusiastic in learning.